CR4 Signaling Contributes to a DC-Driven Enhanced Immune Response Against Complement-Opsonized HIV-1 - Bermejo-Jambrina, Marta; Blatzer, Michael; Jauregui-Onieva, Paula; Yordanov, Teodor E.; Hörtnagl, Paul; Valovka, Taras; Huber, Lukas A.; Wilflingseder, Doris; Posch, Wilfried (Frontiers in Immunology, 2020)
Dendritic cells (DCs) possess intrinsic cellular defense mechanisms to specifically inhibit HIV-1 replication. In turn, HIV-1 has evolved strategies to evade innate immune sensing by DCs resulting in suboptimal maturation and poor antiviral immune responses. We previously showed that complement-opsonized HIV-1 (HIV-C) was able to efficiently infect various DC subsets significantly higher than non-opsonized HIV-1 (HIV) and therefore also mediate a higher antiviral immunity. Thus, complement coating of HIV-1 might play a role with respect to viral control occurring early during infection via modulation of DCs. To determine in detail which complement receptors (CRs) expressed on DCs was responsible for infection and superior pro-inflammatory and antiviral effects, we generated stable deletion mutants for the α-chains of CR3, CD11b, and CR4, CD11c using CRISPR/Cas9 in THP1-derived DCs. We found that CD11c deletion resulted in impaired DC infection as well as antiviral and pro-inflammatory immunity upon exposure to complement-coated HIV-1. In contrast, sole expression of CD11b on DCs shifted the cells to an anti-inflammatory, regulatory DC type. We here illustrated that CR4 comprised of CD11c and CD18 is the major player with respect to DC infection associated with a potent early pro-inflammatory immune response. A more detailed characterization of CR3 and CR4 functions using our powerful tool might open novel avenues for early therapeutic intervention during HIV-1 infection.